458 Blood Loss Following First Time Coronary-Artery-Bypass-Graft (CABG). (12th October 2021) - Ishak, L; Morcos, K; Curry, P
Abstract: Introduction: Blood loss following cardiac surgery is a recognised complication associated with post-operative mortality and morbidity. Aim: To identify parameters associated with blood loss and need for blood transfusion following first time coronary-artery-bypass-graft (CABG). Method: Data was collected retrospectively on 50 patients who underwent a first time CABG between 12/02/2020 – 21/09/2020 at the Golden Jubilee National Hospital (GJNH). Parameters included pre-operative and post-operative haemoglobin, platelets, INR, calcium levels, patient age, body-mass-index (BMI), creatinine clearance (CrCl), presence of co-morbidities, anti-coagulant drug use, cross-clamp time, bypass time, re-exploration rates and number of grafts. Patients who required a blood transfusion post-operatively were compared with those who did not require transfusion. Results: Seventeen of the 50 patients required a blood transfusion. This group had a lower mean post-operative haemoglobin levels (90.82 vs 107.82, p = <0.001), lower mean post-operative platelet levels (138.47 vs 187.09, p = 0.02), higher post-operative INR (1.25 vs 1.15, p = 0.15), higher mean BMI (27.93 vs 30.433, p = 0.063), higher mean renal dysfunction severity grades (0.7 vs 0.3, p = 0.044) and lower mean CrCl (78 vs 97, p = 0.025). The transfused patient group had older mean age (68.29 vs 64.84, p = 0.065) and a longer mean post-operative hospital stay (9.38 vs 6.67 days, p = 0.043). More patients had pre-operative haemoglobin <120 (p = 0.26), post-operative haemoglobin <90 (p = <0.0001) and post-operative platelets <100 (p = 0.0029). One patient in the transfused group died post-operatively. Conclusions: Sub-optimal peri-operative blood levels, renal dysfunction, patient age and patient BMI can influence blood loss and requirement for transfusion following first time CABG.